PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF UNTUK PENINGKATAN KETERAMPILAN MENENTUKAN UNSUR INTRINSIK TEKS FIKSI KELAS V SDN SIDOTOPO WETAN IV/558 SURABAYA - Eva Kurnia Sari; Sujinah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to develop and evaluate the effectiveness and practicality of Canva-based Interactive Learning Multimedia (MPI) for identifying the intrinsic elements of fictional texts in Grade V at SDN Sidotopo Wetan IV/558 Surabaya. Adopting an adapted Borg and Gall R&D model, the research involved 72 students as a population sample. Data collection instruments included validation questionnaires, implementation tests, and user response surveys. The validation results by media and content experts reached an average score of 88.25%, classifying it as highly valid. Field-testing demonstrated high effectiveness, with classical student completeness increasing to 83,3% (60 out of 72 students) and achieving an overall average score of 87.9, well above the established Minimum Criteria (KKTP) of 80. Furthermore, user responses from both teachers and students exceeded 50% across all indicators, indicating that the developed digital multimedia is highly practical and engaging for elementary school language instruction.